Evaluation of the rewarding effects of mitragynine and 7‐hydroxymitragynine in an intracranial self-stimulation procedure in male and female rats. (1st October 2020) - Behnood-Rod, Azin; Chellian, Ranjithkumar; Wilson, Ryann; Hiranita, Takato; Sharma, Abhisheak; Leon, Francisco; McCurdy, Christopher R.; McMahon, Lance R.; Bruijnzeel, Adriaan W.
Highlights: Mitragynine and 7-hydroxymitragynine are not rewarding in the ICSS procedure. A high dose of 7-hydroxymitragynine is aversive in the ICSS procedure. There are no sex differences in the effects of mitragynine and 7-hydroxymitragynine. Morphine is rewarding in the ICSS procedure. Abstract: Background: Kratom (Mitragyna speciosa Korth.) has been used in Southeast Asia for hundreds of years to increase energy, for relaxation, and to diminish opioid withdrawal. Kratom use has recently spread to Western countries. Kratom could potentially be used for the treatment of opioid withdrawal and pain, but more insight is needed into its abuse potential. Therefore, we investigated the rewarding properties of the primary kratom alkaloid mitragynine and its active metabolite 7-hydroxymitragynine, and morphine as a reference drug in male and female rats. These compounds have agonist activity at mu-opioid receptors. Methods: The compounds were tested in an intracranial self-stimulation (ICSS) procedure, which allows for the evaluation of the rewarding/aversive and sedative effects of drugs. Rewarding doses of drugs decrease the brain reward thresholds, and aversive drug doses have the opposite effect. Results: Mitragynine, 7-hydroxymitragynine, and morphine affected the brain reward thresholds. A high dose of 7-hydroxymitragynine (3.2 mg/kg) increased the brain reward thresholds, whereas an intermediate dose of morphine (10 mg/kg) decreased the reward thresholds. 7-Hydroxymitragynine and morphine affected the response latencies. Five mg/kg of morphine increased response latencies. 7-Hydroxymitragynine tended to increase the response latencies, but the post hoc analyses did not reveal a significant effect. There were no sex differences in the effects of mitragynine, 7-hydroxymitragynine, and morphine on the reward thresholds and the response latencies. Conclusions: These initial findings indicate that mitragynine and 7-hydroxymitragynine are not rewarding in the ICSS procedure. The present results suggest that these kratom alkaloids do not have abuse potential.